SOCIOECONOMIC PROFILE AND ACADEMIC PATH OF THE STUDENTS OF FULL DEGREE IN PHYSICAL EDUCATION FROM UFPI (Fiep Bulletin - online, 2012)
Education is a right of all people. But, such fact still doesn’t reflect our current situation because there is so much inequality as in the lower levels of Education like in the most complex. The economic reality of the students in public Higher Education Institutions (HEI) is a reflection of the reality faced by most of the brazilian population, comprising all its contradictions. The objective of this study was to characterize the socioeconomic profile and know the academic path of students of the Full Degree in Physical Education course of the Federal University of Piauí (UFPI). It’s treated of a descriptive type of research with a quantitative approach. The sample consisted of 169 students distributed among the first, third, fourth, sixth and seventh periods of the course, along which was applied a questionnaire divided into three themes: the student's personal data, socioeconomic and educational aspects. The data show that most students are young (18 and 24 years old), single, formed mostly by women. Most of the subjects chose the course of self-interest but there is a discrepancy as to the future area of professional practice (33% scholastic and 34% non-school). The difficulties of staying the course are great because there is predominance of financially needy students (classes D and E) and of these, 34% do not have their own income. Of those who have it, only 19% received financial support from HEI and other extracurricular perform stage with financial assistance less than the minimum wage or have jobs. It is concluded that the students of Physical Education from UFPI are mostly low income and need financial support and teaching to stay and completion of graduation.
Keywords: Vocational Training; Physical Education; Degree